1996
DOI: 10.1007/s004210050125
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of the acute phase response after a marathon race, and the effects of glutamine supplementation

Abstract: Strenuous exercise may be associated with immune suppression. However, the underlying mechanism is not known. A decrease in the plasma level of glutamine, which is utilised at a high rate by cells of the immune system, and an increase in the plasma level of some cytokines may impair immune functions such as lymphocyte proliferation after prolonged, exhaustive exercise. In two separate studies of the Brussels marathon, using similar protocols, the time course of the changes in the plasma concentrations of some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
138
1
10

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(164 citation statements)
references
References 34 publications
15
138
1
10
Order By: Relevance
“…It has been postulated that restoring glutamine levels after prolonged exercise to physiological levels may help the immune system to resist infections. Although oral provision of glutamine, or branched chain amino acids as a glutamine precursor, abolishes the post-exercise plasma glutamine decrease, it has no consistent effect on lymphocyte or neutrophil counts (Rohde et al, 1998;Walsh et al, 2000;Peters et al, 2001a;Krzywkowski et al, 2001a), salivary IgA (Krzywkowski et al, 2001b), oxidative burst activity (Walsh et al, 2000), NKCA (Rohde et al, 1998;Walsh et al, 2000) or plasma IL-6 (Castell et al, 1997;Hiscock et al, 2003) after exercise. Although it was suggested that glutamine could enhance Th1-type immune response in swimmers submitted to 4 weeks of intensive training, there was no significant difference in glutamine levels between athletes who developed URT infection and those who did not (Mackinnon and Hooper, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been postulated that restoring glutamine levels after prolonged exercise to physiological levels may help the immune system to resist infections. Although oral provision of glutamine, or branched chain amino acids as a glutamine precursor, abolishes the post-exercise plasma glutamine decrease, it has no consistent effect on lymphocyte or neutrophil counts (Rohde et al, 1998;Walsh et al, 2000;Peters et al, 2001a;Krzywkowski et al, 2001a), salivary IgA (Krzywkowski et al, 2001b), oxidative burst activity (Walsh et al, 2000), NKCA (Rohde et al, 1998;Walsh et al, 2000) or plasma IL-6 (Castell et al, 1997;Hiscock et al, 2003) after exercise. Although it was suggested that glutamine could enhance Th1-type immune response in swimmers submitted to 4 weeks of intensive training, there was no significant difference in glutamine levels between athletes who developed URT infection and those who did not (Mackinnon and Hooper, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Doses of 1500 mg of vitamin C daily were reported to attenuate the increase in these cytokines after exercise (Nieman et al, 2000b;Peters et al, 2001a) or have no effect (Nieman et al, 2002b) at lower doses of 1000 or 500 mg daily (Nieman et al, 1997b;Peters et al, 2001b). Of the two studies where glutamine was given as a supplement, one study showed glutamine to augment the increase of plasma IL-6 (Hiscock et al, 2003) after exercise, while the other (Castell et al, 1997) did not. Polyunsaturated fatty acids had no effect on plasma TNF-alfa, IL-6, TGF-beta and IL-1ra (Toft et al, 2000).…”
Section: Nutrition and Exercise-induced Immunodepressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em atletas no estado de repouso, Castell e Newsholme (49) observaram que a concentração plasmática de glutamina aumentou cerca de 30 minutos após a ingestão oral de uma solução com L-glutamina (100mg/kg de peso corporal), podendo retornar aos valores basais no decorrer de aproximadamente duas horas.…”
Section: Suplementações Com Glutaminaunclassified
“…They found that the glutamine group showed fewer infections compared to the placebo group. of the immune system is affected by glutamine feeding during the transient immunodepression (suppression that occurs after prolonged, strenuous exercise)" [7]. However, evidence indicates that neutrophils might be implicated instead of lymphocytes as previously thought [5][6][7].…”
Section: Introductionmentioning
confidence: 98%